Evaluating The Suitability Of Euphrates River Water For Animal Consumption In The City Of Samawah Using The Canadian Catalyst: Evaluasi Kesesuaian Air Sungai Eufrat Untuk Konsumsi Ternak Di Kota Samawah Menggunakan Katalis Kanada - Kanbar, Tarteel Faisal Ghaze; Hasan, Mustafa Salah; Mohammed, Anmar Jasim (Universitas Muhammadiyah Sidoarjo, 2025)
The study concluded that the assessment of the Euphrates River water quality in the Samawah area using the Canadian Water Quality Index (CWQI) and water quality standards for animal consumption showed variation in water quality among the studied sites. Site 1 (M1) was classified as